2010
DOI: 10.1007/s00438-010-0513-z
|View full text |Cite
|
Sign up to set email alerts
|

AtfA bZIP-type transcription factor regulates oxidative and osmotic stress responses in Aspergillus nidulans

Abstract: The aim of the study was to demonstrate that the bZIP-type transcription factor AtfA regulates different types of stress responses in Aspergillus nidulans similarly to Atf1, the orthologous 'all-purpose' transcription factor of Schizosaccharomyces pombe. Heterologous expression of atfA in a S. pombe Deltaatf1 mutant restored the osmotic stress tolerance of fission yeast in surface cultures to the same level as recorded in complementation studies with the atf1 gene, and a partial complementation of the osmotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
102
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 87 publications
(113 citation statements)
references
References 75 publications
11
102
0
Order By: Relevance
“…Significantly decreased stress tolerances were found in oxidative stress (MSB, tBOOH and H 2 O 2 )-exposed RWY10.3 (DnapA) cultures ("80 % ,DDA ,"20 %); meanwhile, growth stimulation caused by the overexpression of napA (RWY17.3) was DDA ¡15 % under different oxidative stress treatments. Pyridoxine supplementation increased slightly the oxidative stress resistance of RDIT9.32 (DDA ¡5 %), which was similar to previous findings (Balá zs et al, 2010). (Halliwell & Gutteridge, 2007).…”
Section: Napa Involvement In Sm Is Stress-relatedsupporting
confidence: 91%
“…Significantly decreased stress tolerances were found in oxidative stress (MSB, tBOOH and H 2 O 2 )-exposed RWY10.3 (DnapA) cultures ("80 % ,DDA ,"20 %); meanwhile, growth stimulation caused by the overexpression of napA (RWY17.3) was DDA ¡15 % under different oxidative stress treatments. Pyridoxine supplementation increased slightly the oxidative stress resistance of RDIT9.32 (DDA ¡5 %), which was similar to previous findings (Balá zs et al, 2010). (Halliwell & Gutteridge, 2007).…”
Section: Napa Involvement In Sm Is Stress-relatedsupporting
confidence: 91%
“…As expected, mRNA levels of sod1, catA and cat2 were significantly up regulated. Studies in Aspergilli have demonstrated that both, atfA and atfB, are essentially required to activate catA expression (Balázs et al, 2010;Hagiwara et al, 2016;Lara-Rojas et al, 2011). Herein, we observed higher expression levels of catA due to the over-expression of the atfB gene.…”
Section: Effect Of Piperine On Antioxidant Defense Genes and Fungal Esupporting
confidence: 46%
“…By contrast, in our study, atfB was over expressed while veA levels were decreased suggesting that other factors may influence atfB expression. Finally, atfA, another gene mainly involved in oxidativestress response (Balázs et al, 2010), was also up-regulated. AtfA, belonging also to the ATF/CREB family, permanently resides in the nucleus until activation as a response to oxidative or osmotic stress signals (Lara-Rojas et al, 2011).…”
Section: Piperine Inhibits Afb1 Production and Modulates Bzip Transcrmentioning
confidence: 96%
“…In response to oxidative stress, A. oryzae atfB directly activates the catalase gene, catA (31,49). Consistent with this theme, atf1 and its ortholog aftA activate the catalase gene ctt1 in fission yeast S. pombe and catalase B in A. nidulans, respectively (28,50). ATF/CREB family proteins also activate genes involved in osmotic stress response in S. cerevisiae and S. pombe.…”
Section: Atfb Binds Multiple Aflatoxin Gene Promoters Under Aflatoxinmentioning
confidence: 56%